In situ cathodic activation of V-incorporated NixSy nanowires for enhanced hydrogen evolution. Issue 34 (27th June 2017) - Shang, Xiao; Yan, Kai-Li; Rao, Yi; Dong, Bin; Chi, Jing-Qi; Liu, Yan-Ru; Li, Xiao; Chai, Yong-Ming; Liu, Chen-Guang
Abstract : In situ cathodic activation (ISCA) of V-incorporated Ni x S y nanowires supported on nickel foam (VS/Ni x S y /NF) can be realized in an alkaline hydrogen evolution reaction (HER) process, which provides not only obviously enhanced activity but also ultrahigh stability for HER. Abstract : In situ cathodic activation (ISCA) of V-incorporated Ni x S y nanowires supported on nickel foam (VS/Ni x S y /NF) can be realized in an alkaline hydrogen evolution reaction (HER) process, which provides not only clearly enhanced activity but also ultrahigh stability for HER. The ISCA process is continuous linear sweep voltammetry (LSV) on VS/Ni x S y /NF as a cathodic electrode with gradually enhanced HER activity. The activated VS/Ni x S y /NF (A-VS/Ni x S y /NF) demonstrates enhanced HER activity with an overpotential of 125 mV to drive 10 mA cm −2, which is much lower than that of other samples. It may be predicted that the ISCA-derived amorphous VOOH film covering on A-VS/Ni x S y /NF accelerates the HER process, and NiOOH may protect active sites from decaying, leading to excellent activity and structural stability. However, for single metal sulfides, the ISCA process of nickel or vanadium sulfides is not available, implying that the synergistic effect between Ni and V of VS/Ni x S y /NF may be the key to drive ISCA in alkaline HER. In addition, its ultra-high stability confirms that the stable active sites and nanostructures of A-VS/Ni x S y /NF are derived from ISCA. Therefore, the ISCA of V-incorporated transition metal sulfides in the alkaline HER process may be a facile and promising method to obtain efficient electrocatalysts.